Fostering Moderate Islamic Values: Implementing a Design Model for Counter-Radicalization in Higher Education - Nadlir Nadlir; Ilun Mualifah (UIN Sunan Ampel Surabaya, 2023)
This study delves into the construction of a counter-radicalization model within Islamic higher education, specifically at Sunan Ampel State Islamic University in Surabaya. The imperative to curb the spread of radicalism within campus communities highlights the significance of cultivating a comprehensive grasp of moderate Islam among students. Central to this research is the examination of the Islamic Studies course within the Primary School Teacher Education Program. Employing a research and development methodology, the study employs pre-post test designs, including control groups, to discern the effectiveness of the proposed model. Notably, the course design departs from conventional non-religious subjects, incorporating both direct and indirect instructional approaches. Post-treatment results reveal a noteworthy enhancement in students' exhibition of moderate Islamic attitudes, with performance levels escalating from an initial 60.71% to a promising 70.00%. Statistical scrutiny underscores the model's efficacy, affirming its potency in fostering moderation-based insights among students. Ultimately, this investigation underscores the model's superiority in enhancing students' comprehension in contrast to conventional pedagogical strategies.